On the Threshold of Knowing: Lectures and Performances in Art and Academia - Rainer, Lucia (transcript, 2017)
In this in-depth analysis of artistic and academic lectures and performances, Lucia Rainer features an innovative conceptual and methodological tool that augments Goffman's Frame Analysis with a praxeological perspective. This way, she gives profound insight into how knowledge – as a practice and a concept – is associated with clarity rather than truth. Based on four case studies – including John Cage's unpublished and unabridged audio recording of Lecture on Nothing – the study explores how the concept of lecture performances, which adheres to two frames that never entirely blend, provides a space to (re-)negotiate the artistic-academic relationship.